The Influence of Content Marketing and Brand Image on Satisfaction of Purchasing Pekanbaru Event Organizer Services - Sembiring, Chelsea Amanda; Nasution, Harris Pinagaran (CV. Civiliza Publishing, 2025)
The MICE (Meeting, Incentive, Convention, and Exhibition) industry encourages the growth of event organizer (EO) business as a professional service provider in the design, management, and implementation of events. The city of Pekanbaru as the capital of Riau Province shows a positive development of this industry, marked by the increasing number of EOs that offer a variety of services according to market needs. The use of social media as a marketing channel also affects consumer perception and trust, where Instagram visual content and online reviews on google reviews are important considerations in decision-making. This study aims to determine the influence of content marketing and brand image on the purchase decision of Pekanbaru Event Organizer services. This study uses a quantitative method with data collection techniques through the distribution of questionnaires to 43 respondents who are Pekanbaru Event Organizer clients from 2022 to 2024. The data analysis technique used was multiple linear regression with the help of SPSS software. The results showed that partially, content marketing had a positive and significant effect on purchase decisions with a significance value of 0.037 Meanwhile, brand image did not have a significant effect partially, with a significance value of 0.093. However, simultaneously, both variables had a significant effect on purchasing decisions, with a Fcal value of 7.304 and a significance of 0.002. A determination coefficient value (R²) of 0.231 indicates that content marketing and brand image together are able to explain 23.1% of the variation in service purchase decisions in the company, while the remaining 76.9% is explained by other variables not studied in this study.